SP4.1.8 Patient satisfaction with telephone versus face-to-face consultations during the COVID-19 pandemic. (28th October 2021) - Psaltis, Emmanouil; Tzatzidou, Anastasia; Chua, Yunli; Abdullmalek, Hidayatul; Kanakala, Venkatesh
Abstract: Aims: Patient satisfaction is an important and commonly used indicator for measuring the quality in health care. During the COVID-19 pandemic, several face-to-face appointments in the outpatient clinics have been converted to telephone consultations. The aim of this study was to compare patient satisfaction following telephone consultations over face-to-face appointments in General Surgery. Methods: A retrospective survey on consecutive patients (n = 63) was conducted over the telephone by independent interviewers. Group I (n = 36) consisted of patients who had telephone consultations and Group II (n = 27) of patients who had face-to-face appointments. Patient satisfaction was recorded using the Generic Medical Interview Satisfaction Scale (G-MISS) questionnaire as it has been validated for use in General Surgery. Statistical analysis was performed to assess for any differences between the two groups in the cumulative satisfaction scores and the three dimensions of the G-MISS questionnaire, "relief", "compliance" and "communication". Results: Median, Q1-Q3 of the satisfaction score in Group I (77.3, 62.1-93.3) did not statistically differ compared with Group II (76.5, 62.5-93.3, p = 0.91). "Relief" in Group I (78.1, 57.0-92.9) did not significantly vary compared with Group II (75.0, 53.1-93.7, p = 0.85). "Compliance" in Group I (62.5, 50.0-96.8) was very similar with that in Group II (75.0, 50.0-100.0, p = 0.82). "Communication" in Group I (87.5, 71.8-98.9) was also very similar compared with Group II (87.5, 75.0-100.0, p = 0.74). Conclusions: We demonstrated high levels of patient satisfaction with telephone consultations. Therefore, during the pandemic the services of the outpatient department remain of high quality. Considering the economic benefits to the NHS, telephone consultations might be "here to stay".